Interferon-γ differentially modulates the impact of tumor necrosis factor-α on human endometrial stromal cells - Spratte, Julia; Oemus, Anne; Zygmunt, Marek; Fluhr, Herbert (Reproductive biology, 2015)
The pro-inflammatory T helper (Th)-1 cytokines, tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ), are immunological factors relevant at the feto-maternal interface and involved in the pathophysiology of implantation disorders. The synergistic action of the two cytokines has been described with regard to apoptotic cell death and inflammatory responses in different cell types, but little is known regarding the human endometrium. Therefore, we examined the interaction of TNF-α and IFN-γ in human endometrial stromal cells (ESCs). ESCs were isolated from specimens obtained during hysterectomy and decidualized in vitro. Cells were incubated with TNF-α, IFN-γ or signaling-inhibitor. Insulin-like growth factor binding protein (IGFBP)-1, prolactin (PRL), leukemia inhibitory factor (LIF), interleukin (IL)-6, IL-8, regulated on activation normal T-cell expressed and secreted protein (RANTES) and monocyte chemotactic protein (MCP)-1 were measured using ELISA and real-time RT-PCR. Nuclear factor of transcription (NF)-κB and its inhibitor (IκBα) were analyzed by in-cell western assay and transcription factor assay. TNF-α inhibited and IFN-γ did not affect the decidualization of ESCs. In contrast, IFN-gamma differentially modulated the stimulating effect of TNF-alpha on cytokines by enhancing IL-6, RANTES and MCP-1 and attenuating LIF mRNA expression. These effects were time- and dose-dependent. IFN-γ had no impact on the initial activation of NF-κB signaling. Histone-deacetylase activity was involved in the modulating effect of IFN-γ on RANTES secretion. These observations showed a distinct pattern of interaction of the Th-1 cytokines, TNF-α and IFN-γ in the human endometrium, which could play an important role in the pathophysiology of implantation disorders.
Gesehen am 22.06.2020